A study on maxillary sinus dimensions by computed tomography in population of Tamil Nadu - N Muthukumaravel; K Y Manjunath (Wolters Kluwer Medknow Publications, 2016)
Background and aims: Maxillary sinuses are the largest of the paranasal sinuses known for variability in their dimensions. The maxillary sinus dimensions can be better ascertained in living by using computed tomography instead of plain radiography. This study was planned for highlighting the variations in the dimensions of the maxillary sinuses of population of Tamil Nadu region. The aims of the present study were to estimate dimensions of the maxillary sinuses on computed tomographic (CT) scan of the head of patients from Tamil Nadu and to compare the data gender wise and sidewise. Material and methods: Maximum width, height and depth of maxillary sinus of both sides were measured in CT - head images of 100 males and 100 females of 20-50 years of age in Tamil Nadu. Comparison of data between genders and sides by applying unpaired student "t" test was done. Results : The mean depth, height and width of both right and left maxillary sinuses were comparatively less in females than the males and the difference was found to be statistically significant (P< .0001). On comparison between the sides of maxillary sinuses, the depth and the height of maxillary sinus did not show any significant difference in the measurements (p >.05), whereas the width of the left side (23.96 mm) was higher than that of the right side (23.69) and the difference was found to be statistically significant (P<.05). The combined average maxillary sinus dimensions (in mm) for both genders in the study population of Tamil Nadu are as follows: Right side depth: 33.71 ± 1.00; Left side depth : 33.65 ± 1.22; Right side height: 34.66 ± 2.71; Left side height: 34.74 ± 2.48; Right side width: 23.69 ± 0.78 and Left side width: 23.96 ± 0.86. Conclusion: The dimensions of maxillary sinuses in males were found to be larger than those of females and this difference was statistically significant. The average width of the maxillary sinuses on the left side is significantly more than that of right sided sinuses. Computed tomography measurements of maxillary sinuses may be useful in gender determination.